This preview shows pages 1–6. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: 2DOF systems Prototype 2DOF system: k 1 c1 m 1 c2 m 2 k 2 F2 F1 x2 x 1 FBD1 m 1 F1 fS1 fD 1 fD 2 fS2 ) ( ) ( 1 2 2 1 2 2 1 1 1 1 1 2 2 1 1 1 1 1 x x c x x k x c x k F f f f f F x m D S D S  + + = + + = FBD2 m 2 F2 fS2 fD 2 ) ( ) ( 1 2 2 1 2 2 2 2 2 2 2 2 x x c x x k F f f F x m D S  = = Equations of motion: 2 2 2 1 2 2 2 1 2 2 2 1 2 2 1 2 1 2 2 1 2 1 1 1 ) ( ) ( F x k x k x c x c x m F x k x k k x c x c c x m = + + = + + + + Matrix form: =  + +  + + 2 1 2 1 2 2 2 2 1 2 1 2 2 2 2 1 2 1 2 1 F F x x k k k k k x x c c c c c x x m m F x x x = + + K C M : form General Note that mass, damping and stiffness matrices are symmetric, M is diagonal, and C and K are full. EOMs are coupled through C and K, but not through M. Suppose we use different coordinatesinstead of x1 and x2, lets use x1 and y2 x2x1 : FBD1 m 1 F1 fS1 fD 1 fD 2 fS2 2 2 2 2 1 1 1 1 1 1 2 2 1 2 2 1 1 1 1 1 2 2 1 1 1 1 1 ) ( ) ( y c y k x c x k F x x c x x k x c x k F f f f f F x m D S D S + + = + + = + + = FBD2 m 2 F2 fS2 fD 2 ) ( ) ( ) ( 2 1 2 2 2 2 2 2 1 2 2 1 2 2 2 2 2 2 2 2 y x m y c y k F x x c x x k F f f F x m D S + = = = = Equations of motion: 2 2 2 2 2 2 2 1 2 1 2 2 1 1 2 2 1 1 1 1 F y k y c y m x m F y k x k y c x c x m = + + + = + + Matrix form: =  +  + 2 1 2 1 2 2 1 2 1 2 2 1 2 1 2 2 1 F F y x k k k y x c c c y x m m m Looks like weve lost symmetry. Is there a way to get it back, with x1 and y2 as coordinates? (Without ruining the equations!) What changes are legal? We can: multiply an equation by something, combine (add?) the two equations, as long as we dont change the information they express. Here they are again: + = + + + 2 2 1 2 1 2 1 2 1 2 1 2 1 2 2 2 2 1 F F F y x k k y x c c y x m m m m m What if we replace the first equation by the sum of the two?...
View
Full
Document
This note was uploaded on 09/18/2011 for the course ASE 365 taught by Professor Staff during the Spring '10 term at University of Texas at Austin.
 Spring '10
 Staff

Click to edit the document details